Microstructural, Raman, and Magnetic Investigations on Ca-doped ZnO Nanoparticles - Mrabet, S.; Ihzaz, N.; Bessadok, M. N.; Vázquez-Vázquez, C.; Alshammari, M.; El Mir, L. (Journal of inorganic and organometallic polymers and materials, 2024)
We report on the effects of Ca doping on the structural and magnetic characteristics of ZnO oxide nanoparticles (NPs) (Zn 0.96 Ca 0.04 O, called hereinafter ZCO). The hexagonal wurtzite symmetry ZnO phase nanostructure’s presence in the P6 3 mc space group is confirmed by X-ray diffraction analyses employing Rietveld refinement. No Ca-rich clusters or separated secondary phases were observed. This assertion is supported by analyses of transmission electron microscopy (TEM) images as well as Raman spectra of ZCO taken at ambient temperature. The crystallite size and lattice strain were assessed using the Williamson-Hall (W–H) method with a variety of models, including the uniform deformation model (UDM), uniform stress deformation model (USDM), and uniform deformation energy density model (UDEDM), as well as the size-strain plot (SSP) method and morphological observations using TEM images. Magnetization (M) as a function of temperature (T) and magnetic field (H) reveal that the sample exhibits both ferromagnetic (FM) and antiferromagnetic (AFM) ordering; the M vs. T curve is well fitted by a combined equation derived from the three-dimensional (3D) spin wave model and Curie–Weiss law, which confirms the existence of a mixed state of FM and PM phases. By using the polaronic percolation of bound magnetic polarons (BMP) generated by oxygen vacancies (V O ) defects, magnetic interaction may be explored and described quantitatively.